Strategi Bauran Promosi Lokananta Surakarta untuk Meningkatkan Kunjungan Wisatawan Lokal - Dewi, Luh Putu Angelina Purnama; Vanel, Zon (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Competition in the industrial sector is getting tighter, but on the other hand, there is an imbalance in the increase in visit numbers. Business competition is a challenge and threat to survival. Lokananta Surakarta carries out several strategies because this has a crucial role in encouraging an increase in the number of visitors. This research is a qualitative descriptive research, with data collection methods using interviews and observation. The aim of carrying out this research is to find out and explain the promotional mix strategy used by Lokananta Surakarta to increase the number of local tourists. The results of this research show that there is a promotional mix used to increase visitors, namely advertising, sales, direct marketing, sales promotions and public relations. Sales promotion activities carried out include discounts, packages and merchandise which most persuade people to be more interested in visiting.